Historicism, metaphysics, personology in non-classical epic “Telluria” by V. Sorokin - Бабай, Павел Николаевич (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The article surveyed the temporal pattern of Sorokin’s art system in 2000s - 2010s. The novel “Telluria” in this context is analyzed in terms of the type of non-classical epic poetics. Epic narrative structure interacts with the medial author's project, which integrates to novelistic narrative additional projection of metha-aesthetic reflection. Central to the novel image-symbol of tellurium nail appears as the art adequate to hybrid structure of epic narrative and intermedia project.